The Earthquake Effects on VemacularBuildings: An Examplary Study in Çerkeş/Çanlar - Semiz, Hayriye Nisa; Arslan, Burak (My University, 2018)
Çerkeş, located on the border between Central Anatolia and Western Black Sea regions, is a district o f Çankırı.The settlement which has been an important commercial center due to its location was ruled by the Ottomans beginning from the fifteenth century. In the seventeenth century, Çerkeş gained significance with the result of that it was among the most important military destinations during the Baghdad and Revan campaigns.The building complex including a mosque, and a public bath constructed in this period, and has been indicated the old center o f the town.Moreover, the urban fabric surrounding the center has been reflecting the local architectural characteristics of the region. However, Gerede Earthquake in 1944, which caused big damages and losses at the Western Black Sea Region, also resulted in big devastations on the monumental and vernacular buildings in Çerkeş.In this research, the House of Uyanık Family, which is among the survived examples o f vernacular architecture in Çerkeş, has been studied. The first construction date of the house isn’t known. Yet, the building is probably dated to the end of the nineteenth century considering the information given by the family. The house constructed in timber frame is rectangular in plan (approximately 12,80 m x 10,50 m) and surrounded with a garden on the north. The building was affected by the earthquake in 1944, and some parts were damaged severely. Consequently, Uyanık Family built a small house in the garden for temporary use. After some repairs and changes, the family continued to live in the house. Within this study, the house has been documented in detail and identified its original materials and construction techniques. The earthquake effects on the vernacular buildings in this region has been examined considering the structural damages in the House of Uyanık Family with the result of the earthquake.
Keywords: Vernacular Architecture; Architectural Documentation; Earthquake Effects; Restoration